1976
DOI: 10.2135/cropsci1976.0011183x001600010008x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Model of Cotton Yield1

Abstract: A model of cotton (Góssypium sp) lint yield that equated yield to the volume of a parallelepiped with three dimensions was developed by Kerr. The model is extended to basic units by dividing the axes of the parallelepiped and the seed is recognized as the basic unit of yield. Yield per seed, per boll, and per unit area of land can be stated in equation form by using the divisions of the axes. The relative contributions of the primary lint yield components decrease as the complexity of the model increases from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 0 publications
2
39
0
2
Order By: Relevance
“…New spinning and weaving technologies in the textile industry mandate that plant breeders and geneticists develop cultivars of upland cotton with improved fiber quality, especially fiber strength, fiber length, and length uniformity without sacrificing yield potential. However, previous studies report that the negative association resulting from the linkage connections and pleiotropic effects between lint yield and fiber quality, and especially between yield and fiber strength, has hampered the simultaneous improvement of these two important characteristics in cotton (Scholl and Miller, 1976;Worley et al, 1976;Culp et al, 1979;Green and Culp, 1990;Basal and Smith, 1997;Smith and Coyle, 1997). In cotton, increasing one of the yield components often results in decreasing other fiber quality component(s) because of balanced compensation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New spinning and weaving technologies in the textile industry mandate that plant breeders and geneticists develop cultivars of upland cotton with improved fiber quality, especially fiber strength, fiber length, and length uniformity without sacrificing yield potential. However, previous studies report that the negative association resulting from the linkage connections and pleiotropic effects between lint yield and fiber quality, and especially between yield and fiber strength, has hampered the simultaneous improvement of these two important characteristics in cotton (Scholl and Miller, 1976;Worley et al, 1976;Culp et al, 1979;Green and Culp, 1990;Basal and Smith, 1997;Smith and Coyle, 1997). In cotton, increasing one of the yield components often results in decreasing other fiber quality component(s) because of balanced compensation.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of the seed surface area was performed using Hodson's (1920) estimation table. Within-boll yield components were calculated by the ontogenetic yield model of Worley et al (1976), which is also reported in Basal and Smith (1997). These components were as follows: boll weight (BW), seed cotton weight per sample/number of bolls in the sample; lint percent (LP), 100 x sample lint weight/sample seed cotton weight; seed index, weight of 100 fuzzy seeds; seeds/boll (S/B), BW·(1-LP/100/seed index/100); converted micronaire (CM), HVI micronaire·39.36·10 -6 (converts HVI micronaire to g m 1 ); mean fiber length (ML), UI·UHM·10 -3 (converts units from mm to m); surface area per seed (SAS), estimated from Hodson's (1920) The GCA effects of the parents and the SCA effects of the hybrids were estimated using the line × tester analyses method described by Kempthorne (1957).…”
Section: Introductionmentioning
confidence: 99%
“…Lint yield is determined by bolls per square meter, seeds per boll, and lint per seed (Worley et al, 1974;Worley et al, 1976). Although the yield component, bolls per square meter, is an inherited trait, it is highly depended on plant density, and environmental effects on this component are large (Meredith and Bridge, 1973).…”
Section: Gene Action and Combining Ability For Lint Yield And Fiber Qmentioning
confidence: 99%
“…Although the yield component, bolls per square meter, is an inherited trait, it is highly depended on plant density, and environmental effects on this component are large (Meredith and Bridge, 1973). Lint yield is determined by seed cotton yield and lint percentage, and a number of within boll yield components contributing to lint yield including seeds per boll, lint per seed, lint weight per unit seed surface area, fibers per seed, and fibers per unit seed surface area (Worley et al, 1976;Coyle and Smith, 1997). Fiber quality is a series of fiber properties which determine the spinnability of fibers and the efficiency of the high speed spinners in the modern textile industries.…”
Section: Gene Action and Combining Ability For Lint Yield And Fiber Qmentioning
confidence: 99%
“…The seed index (the weight of 100 seeds) is related to seed cotton yield (Rahman et al, 1991), while the number of seeds per boll is recognised as the largest contributor to lint yield after the number of bolls per unit area (Worley et al, 1974(Worley et al, , 1976. The desirability of a larger number of seeds per boll has been emphasised as a requirement for greater seed surface areas, and hence lint production within the boll (Culp and Harrell, 1975;Harrell and Culp, 1976).…”
Section: Introductionmentioning
confidence: 99%